Representasi Kekuatan, Kecerdasan, dan Cita Rasa Perempuan: Analisis Wacana pada Film “The Iron Lady” - Wahyuningtyas, Bhernadetta Pravita (Humaniora, 2014)
People’s perception about women describes how women tend to be labelized with various drawbacks. Futhermore, many films put women as appendages to satisfy the desire of seeing the physical polish only, without portraying positive side of a woman which actually represents her personal integrity. Nevertheless, the struggle of women to prove their existence is unstoppable, such as in “The Iron Lady” movie. The movie intends to persuade women that they need to pump out the power within them to boldly express their thoughts, come out from the mutedness and show their superiority, in smart ways, woman way. Besides, the movie shows some gender imbalances in Parliament and political life which are synonymous with patriarchal ideology. The movie also shows the struggle against the suppression and mutedness of women with the feminist existentialist concept. This study used critical paradigm with Roland Barthes’ semiotic discourse analysis. Research reveals how women represented in "The Iron Lady" and how symbols or values of women should be represented. Results show that women can actually defend themselves and even more after understanding the suppressions. Amid the crush and the dominance of parliamentary colleagues, Thatcher was able to align her position. Though overall ridiculed, doubted, and disbelieved her ability, she took the duty and responsibility as politician and stateswoman. Woman, who is able to oversee, maintain and nurture the country, even stronger, more resilient, and more manly than men.